A Real‐Time Image‐Based Approach to Distinguish and Discriminate Apoptosis from Necrosis. Issue 1 (21st February 2018) - Lekshmi, Asha; Varadarajan, Shankara Narayanan; Lupitha, Santhik Subhasingh; Nair, Mydhily; Chandrasekharan, Aneesh; Santhoshkumar, T.R.
Abstract: Recent cell biology studies reveal that a cell can die through multiple pathways via distinct signaling mechanisms. Among these, apoptosis and necrosis are two distinct cell death pathways, and their detection and discrimination is vital in the drug discovery process and in understanding diverse biological processes. Although sensitive assays for apoptosis and necrosis are available, it is extremely difficult to adapt any of these methods to discriminate apoptosis‐inducing stimuli from necrosis‐inducing stimuli because of the acquisition of secondary necrosis by apoptotic cells when they are not phagocytosed. Essentially, any assay for discriminating apoptosis and necrosis needs to be carried out in real‐time kinetic mode. Caspase 3 or 7 activation is observed in the majority of apoptotic cell death. Similarly, the absence of caspase 3/7 activation and cell membrane leakage are the two prominent indicators for necrotic cell death or necroptosis. The programmed form of necrosis, called pyroptosis, is also accompanied by membrane leakage and most often associated with activation of specific caspases such as caspase 1, 4, or 11, but not through caspase 3/7 activation. Here, a robust and sensitive real‐time method is described to distinguish and discriminate apoptosis from necrosis. The assay utilizes stable integration of a genetically encoded fluorescence resonance energy transfer (FRET) probe for caspase 3/7 activation and the mitochondrion‐targeted DsRed to identify necrotic cells. Caspase activation is determined by cleavage of the FRET probe; loss of soluble FRET probe with retention of mitochondrial red fluorescence indicates necrosis. This unit describes an important protocol for the generation of sensor cells expressing both probes, followed by detailed analysis of apoptosis and necrosis by microscopy imaging, confocal imaging, high‐throughput imaging, and flow cytometry. © 2018 by John Wiley & Sons, Inc.